Implementasi Akuntansi Keuangan Sektor Publik pada Instansi Pemerintah - Evi Susanti; Hagmy Nurma Yolandasari; Putri Meilani; Sugiyanto (CV. Creative Tugu Pena, 2024)
Implementation refers to concrete steps and the process of applying a concept, plan, or solution into real-world practice. In the context of the public sector, implementation includes the process of applying policies, programs, or projects within government or public institutions. The implementation process requires coordination, resource management, and continuous evaluation to ensure the success of the application. Financial accounting implementation in the public sector plays a crucial role in supporting transparency, accountability, and efficiency in managing public entity finances. However, government agencies often face complex challenges in implementing financial accounting systems, such as complex regulations, unclear procedures, and the need for adequate resources. Therefore, this research aims to explore and analyze the implementation of financial accounting in government institutions to identify specific barriers and provide recommendations to improve the effectiveness and efficiency of financial accounting systems in the public sector.